Trends analysis of birth weight of newborn babies born to mothers of different ethnicities of Tripura: a facility-based observational study - Debbarma, Bikash; Tripura, Amar; Murasing, Krishi K.; Baidya, Subrata (International Journal of Research in Medical Sciences, 2025)
Background: There is little known about the ethnic disparity, which is one of the social determinants of low birth weight in India. This issue was not extensively studied, especially in North-east India. The study aimed to analyse the birth weight trends of newborn babies born to different ethnicities in Tripura. Methods: A cross-sectional study was conducted in the West Tripura District of Tripura, capturing birth records from 2017 to 2022 among mothers who went through institutional normal vaginal delivery. A 1520 delivery case record form was used to record all birth events, and they were analysed using both descriptive and inferential statistics. Ethical approval was taken from the Institutional Ethics Committee, AGMC, Tripura. Results: In total, 1520 delivery cases were recorded as normal vaginal delivery. The mean birth weight (kilogram) of newborn babies among Tribal mothers is 3.14±0.46 kgs, Bengali communities’ mothers is 2.83±0.38 kgs, and Tea tribe mothers is 2.76±0.42 kgs. The difference in the mean birth weight of newborns among different ethnicities is found to be statistically significant (p-value 0.008). There was a declining trend in the year 2020-2021 (post-COVID era). The low-birth-weight rate was higher among the tea tribe and the Bengali communities than among Tribal babies (p-value 0.000). Conclusions: The low birth weight was comparatively lower among the tribal community than the tea tribe and the Bengali community. The study suggested taking specific interventions against low birth weight, targeting the marginalized population.